From Innovation and Compatibility to The Intention to Adopt Mobile Payment with User Expectations as The Mediating Factor - Lady, Lady; Lie, Kelvin; Hesniati, Hesniati; Candy, Candy (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
With the rapid growth of mobile payment transactions in Indonesia, it is imperative to understand the factors influencing user acceptance to optimize product development and marketing strategies. This study seeks to examine these factors through the lens of the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework, specifically investigating the effects of effort expectancy (EE), performance expectancy (PE), social influence (SI), hedonic motivation (HM), compatibility (Comp), and innovation (Innv) on behavioral intention (BI). This study employs a quantitative methodology with purposive sampling, gathering data through online surveys from residents of Indonesia, resulting in a sample of 325 respondents who have utilized mobile payment systems. Data analysis employed Partial Least Squares (PLS) using SmartPLS software. The results indicate that EE significantly influences BI, while PE, SI, and HM do not. Additionally, Comp and Innv were found to positively impact PE, EE, and BI. A noteworthy finding is that Comp significantly influences BI, with EE acting as a mediator.